2005
DOI: 10.1159/000084314
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Aspects of the Spatial Distribution and Morphological Characteristics of the Sea Bass (<i>Dicentrarchus labrax </i>L.; Teleostei, Serranidae) Trunk Lateral Line Neuromasts

Abstract: The results presented herein report quantitative data relative to the distribution and morphological characteristics of both types of neuromasts encountered on the trunk lateral line of the sea bass (Dicentrarchus labrax, L.). These data were obtained from scanning electron micrographs. They indicate that, as expected, each modified scale of the sea bass possessed a single canal neuromast with long axis oriented parallel to the fish’s long axis. In contrast to several fish species, two thirds of superficial ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 121 publications
0
8
0
Order By: Relevance
“…Note that different regions exhibit different hair cell polarizations. nidae, Lampetra, and Danio rerio, orientation of sensory epithelia in superficial neuromasts on the trunk was also either rostro-caudal or dorsoventral (Schwartz and Hasler, 1966;Peters, 1973;Mü nz, 1979;Lane and Whitear, 1982;Blaxter et al, 1983;Lannoo, 1987;Webb, 1989c;Coombs and Montgomery, 1994;Webb and Shirey, 2003;Lopez-Schier et al, 2004;Faucher et al, 2005). Lepisosteus has two lines of superficial neuromasts in which all sensory epithelia are oriented dorsoventrally (Song and Northcutt, 1991), Astyanax has vertical rows of superficial neuromasts on the scales with a rostro-caudal orientation of the sensory epithelia (Teyke, 1990), and Cottus bairdi has lines of superficial neuromasts on the trunk with sensory epithelia that are oriented rostro-caudally or dorso-ventrally (Janssen et al, 1987).…”
Section: Species Comparisonmentioning
confidence: 99%
“…Note that different regions exhibit different hair cell polarizations. nidae, Lampetra, and Danio rerio, orientation of sensory epithelia in superficial neuromasts on the trunk was also either rostro-caudal or dorsoventral (Schwartz and Hasler, 1966;Peters, 1973;Mü nz, 1979;Lane and Whitear, 1982;Blaxter et al, 1983;Lannoo, 1987;Webb, 1989c;Coombs and Montgomery, 1994;Webb and Shirey, 2003;Lopez-Schier et al, 2004;Faucher et al, 2005). Lepisosteus has two lines of superficial neuromasts in which all sensory epithelia are oriented dorsoventrally (Song and Northcutt, 1991), Astyanax has vertical rows of superficial neuromasts on the scales with a rostro-caudal orientation of the sensory epithelia (Teyke, 1990), and Cottus bairdi has lines of superficial neuromasts on the trunk with sensory epithelia that are oriented rostro-caudally or dorso-ventrally (Janssen et al, 1987).…”
Section: Species Comparisonmentioning
confidence: 99%
“…Two subpopulations of neuromasts as presumptive canal neuromasts and superficial neuromast can be distinguished after a subsequent maturation. The size, shape and location of the presumptive canal neuromasts predict the localization where the lateral line canals will be present (Bird & Webb, ; Faucher, Lagardere, & Aubert, ; Poling & Fuiman, ; Siregar, ; Webb, ; Webb & Shirey, ).…”
Section: Introductionmentioning
confidence: 99%
“…While the superficial neuromasts change their number and aspect, even if the size remains small, and do not change their localization throughout lifespan (Faucher et al., ; Higgs & Fuiman, ), it is well known that the final step of the development of the lateral line, the canal morphogenesis, starts only in late‐stage larvae and its morphological changes and differentiation continues during the juvenile stages (Becker et al., ). Every individual presumptive canal neuromasts becomes enclosed in a bony canal segment following a process of intramembranous ossification (Bird & Webb, ; Tarby & Webb, ; Webb & Shirey, ).…”
Section: Introductionmentioning
confidence: 99%
“…This study has demonstrated post‐embryonic increases in total neuromast number and the generation of distinctions in the size and shape of presumptive canal and superficial neuromasts in Tramitichromis and Aulonocara . This has been shown in other cichlids (Peters, ; Münz, ; Webb, ), and in zebrafish (e.g., Webb and Shirey, ), three‐spined stickleback (Wark and Peichel, ), and other teleost taxa (e.g., Janssen et al, ; Puzdrowski, ; Song and Northcutt, ; Poling and Fuiman, ; Faucher et al, ). This study has also shown that after their initial differentiation in larvae, presumptive canal neuromasts do not increase in number, but change in shape and increase in size, and that superficial neuromasts stay relatively small, but continue to increase in number through the larval and juvenile stages (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…Presumptive canal neuromasts increase in size and change shape (e.g. Disler and Smirnov, ; Vischer, ; Blaxter and Fuiman, ; Webb, ; Siregar, ; Poling and Fuiman, ; Webb and Shirey, ; Faucher et al, ; Bird and Webb, ) and their locations predict where the lateral line canals will form. Superficial neuromasts will remain on the skin throughout life and may change shape and increase in number, but tend to stay small in size (e.g., Blaxter and Fuiman, ; Harvey et al, ; Higgs and Fuiman, ; Faucher et al, ).…”
Section: Introductionmentioning
confidence: 99%